Polymorphism, gigantism, and cannibalism, one stylonychid ciliate (Ciliophora, Hypotricha) to rule them all - Omar, Atef; Jang, Seok Won; Jung, Jae-Ho (Frontiers in Microbiology, 2023)
The morphology, ontogenesis, and molecular phylogeny of the polymorphic and cannibalistic giant forming Tetmemena polymorpha n. sp., found in a brackish water sample in South Korea, were investigated. The present species has long been misidentified as “Oxytricha bifaria”. The new investigation shows that the species produces three morphologically different morphs. The small morph is bacterivorous and characterized by the small body size, the slim body, and it is found only in the stationary and decline phases of the culture. The large morph has a wide body, larger oral apparatus, and feeds on small eukaryotes such as yeast cells and small ciliates, it divides very quickly and produces the other two morphs and found in the exponential phase of the cultures. The giant morph is characterized by the huge body and oral apparatus, it feeds on the small morph cells of the same species and other ciliates, and occurs together with the small morph. Phylogenetic analyses based on the 18S rRNA gene sequences show that the new species is placed in a sister subclade to that containing other Tetmemena sequences. Moreover, Tetmemena indica Bharti et al., 2019 nov. stat. is raised to species level based on the differences in the cyst morphology and the dorsal ciliature to the authoritative Tetmemena pustulata population.